Influence of Magnetic Frequency on the Thermal Behaviour of Heat Transfer Equipment - Sami, Samuel (Journal of Technology Innovations in Renewable Energy, 2014)
This paper presents a description of the mathematical model developed to predict the natural frequency of a particular refrigerant or refrigerant mixture and magnetic field frequency using the one-dimensional fluid flow conservation equations. The results show the dependence of the Nusselt number on the Reynolds number in the presence and absence of magnetic field. However, the results also provide evidence of enhanced heat transfer and heat flux under magnetic field compared to without magnetic field. In addition, the results presented in the paper clearly provide evidence that the heat transmission has been consistently enhanced when magnetic field is applied. It also appears that heat transfer enhancement is greater at higher Nusselt numbers.